The Vulnerability of Occupational Health of Women Home Workers: A Study in Labor-Intensive Industries in Penjaringan, North Jakarta - Rifyana, Evania Putri (Yayasan Jurnal Perempuan, 2019)
Labor-intensive industries oriented to low prices, has a strategy of reducing labor costs to compete in a competitive market. To streamline the production burden, the company issues a portion of its production commodities to workers outside the factory, in this case homeworkers. The majority of homeworkers are poor women who live around industrial areas. Through a qualitative approach, this study wants to find out the working conditions of women homeworkers working in labor-intensive industries, especially in the shoe sector, in the slums of the Capital City of Jakarta, namely the Penjaringan area, North Jakarta. The study found that women homeworkers do not have access to proper occupational health, making their conditions vulnerable. This vulnerability is influenced by poor working environment conditions, inadequate Health and Safety (K3), and the absence of social protection and security for women homeworkers. In addition, the house, which is used as a production space on a massive scale, also has implications for the daily survival of women homeworkers and their families.